Comparison Equating Method Based on Sample Size - Iriyadi, M.Pd., Dr. Deni; Hartati, Hevriana; Rustam, Ahmad (Yayasan Almubarak Fil Ilmi, 2023)
The purpose of this research is to compare the linear technique to the equipercentile method in terms of the variance of equalization scores using a sample size of one hundred and three different test lengths of twenty-five, twenty-nine, and thirty minutes respectively. In this particular investigation, the value of the variance of the equalization score serves as the dependent variable, while the equalization technique and the duration of the exam serve as the independent variables. A learning outcome exam for physics was used as the instrument of assessment in this particular research project. The participants were high school students. The replies of all of the people who took part in the study and worked on the several test sets that the researcher had put together constituted the study's population. The research sample consisted of the replies provided by the students for each package, for a total of one hundred responses. These responses were selected using a random selection method that included returns, and the process was repeated thirty times. We put the study hypothesis through its paces by employing comparative hypothesis testing in conjunction with t-test analysis. The findings indicated that the variance values of the equalized results obtained via the application of the linear technique were lower than the variance values obtained through the application of the equipercentile approach for test durations of 20, 25, and 30 when there was a sample size of 100.